2020
DOI: 10.1016/j.ijoa.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

An educational intervention about the classification of penicillin allergies: effect on the appropriate choice of antibiotic therapy in pregnant women

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This finding indicates that physicians might be considerably more cautious when prescribing antibiotics for pregnant women and this cautiousness might have a greater effect on antibiotic prescriptions for conditions that only sometimes justify antibiotic use, resulting in potential undertreatment of some infectious conditions. This undertreatment could have harmful effects on maternal and fetal health [ 1 , 2 , 17 ], as infections may increase both maternal and neonatal mortality [ 2 ] and are associated with an increased risk of adverse pregnancy outcomes including spontaneous abortion, prematurity and low birth weight [ 1 , 2 , 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that physicians might be considerably more cautious when prescribing antibiotics for pregnant women and this cautiousness might have a greater effect on antibiotic prescriptions for conditions that only sometimes justify antibiotic use, resulting in potential undertreatment of some infectious conditions. This undertreatment could have harmful effects on maternal and fetal health [ 1 , 2 , 17 ], as infections may increase both maternal and neonatal mortality [ 2 ] and are associated with an increased risk of adverse pregnancy outcomes including spontaneous abortion, prematurity and low birth weight [ 1 , 2 , 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are among the most commonly prescribed medications in pregnant women for infectious diseases [ 1 , 2 ], which, if untreated, would increase maternal and neonatal mortality and significant fetal risks [ 1 , 2 , 3 ]. In some developed countries, the proportion of pregnant women receiving at least one antibiotic prescription during pregnancy can be as high as 50% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We included 30 primary studies that assessed the frequency of cefazolin allergy in series of patients with self-reported or confirmed penicillin allergy (Table 1). The included primary studies had been published between 1976 and 2020, assessing a total of 6001 participants. In 9 studies, penicillin allergy was confirmed by diagnostic testing (skin, in vitro, and/or drug challenges).…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, 18,20,22,23,25,31,32,34,[37][38][39][40]44 cefazolin allergy was assessed by means of skin tests or drug challenges, whereas prophylactic or therapeutic introduction of cefazolin occurred in 18 studies. 17,19,21,24,[26][27][28][29][30]33,[35][36][37][41][42][43]45,46 Cefazolin allergy was identified in 44 participants, resulting in a meta-analytical frequency of 0.7% (95% CrI, 0.1%-1.7%; I 2 = 74.9%) (Figure 2A). Such frequency was lower for participants with self-reported penicillin allergy (0.6%; 95% CrI, 0.1%-1.3%; I 2 = 54.3%) than for those with confirmed allergic reactions (3.0%; 95% CrI, 0.01%-17.0%; I 2 = 88.2%) (OR, 0.4; 95% CrI, 0.02-1.8; 92% probability of OR <1).…”
Section: Frequency Of Cefazolin Allergy In Patients With Penicillin A...mentioning
confidence: 99%
“…A thorough allergy history can differentiate allergies from adverse reactions and, if present, determine the type of MOTS-CLÉS : allergie, anaphylaxie, bêtalactamine, dossier de santé électronique, gestion antibiotique, réactivité croisée, pénicilline antibiotic prescribing guideline for patients with penicillin or cephalosporin allergies (24). Another study demonstrated that providing a short educational presentation of the guideline increased the rate of appropriate antibiotic treatment selection, predefined on the basis of level of allergy risk, by 50% (25). Another approach has been to update prescribing alerting rules to reflect this change in practice.…”
Section: Introductionmentioning
confidence: 99%